(untitled) (e-Journal of Linguistics, 2024)
During his life, humans always communicate with each other. This has been going on from the past until now and will continue into the future. There are always developments in language. We are required to always adapt to the environment. The COVID-19 pandemic also requires us to adapt to the environment. Not only our life behavior has changed, our language behavior is also affected due to the changes in the order of our lives, especially in terms of the use of technology. The lexicon that did not exist before then appears, the lexicon that used to exist has a different meaning during the pandemic. The “zoom” lexicon used to mean only zooming in, but nowadays it has a different meaning. Data lexicon during the pandemic which is rooted from “zoom” lexicon can occupy various word classes in the use of Indonesian.